Additively manufactured lightweight coaxial to circular waveguide transition for linearly polarized microwave systems - Hasan Muhammad Fahad; He Huang; Ray Tahir Mushtaq; Khalid A. Al-Ghamdi (Scientific Reports)
Abstract Waveguides and transitions provide efficient, low-loss microwave transmission across a target frequency band for space communications and radar. However, traditional waveguide transitions suffer from impedance mismatch, higher-order mode excitation, field distortion, and complex-geometry fabrication constraints. This study addresses these issues by developing a Ku-band low-cost coaxial-to-circular waveguide transition prototype, fabricated by Fused Filament Fabrication (FFF), followed by electroless-metallization. We present a novel coaxial-to-rectangular-to-elliptical-to-circular transition topology with an integrated septum for a split-waveguide structure. The entirely conductive PLA filament-based 3D-printed structure with subsequent silver-epoxy metallization features an E-plane cut halves, employing optimized 3D-printing and geometric design parameters. The hybrid design simplifies manufacturing, streamlines metallization, and enhances RF performance through suppressing higher-order modes by 25 dB, improving return loss to better than − 15 dB, reducing attenuation to as low as 0.145dB/m, minimizing electromagnetic discontinuities, and increasing polarization isolation by 30dB for linearly-polarized applications while ensuring smooth field propagation. The lightweight, cost-effective design enables early testing and highlights future implementation with space-grade materials like PEEK/Ultem® that could enable rugged, low-mass alternatives to conventional waveguides. These findings empower a sustainable approach to custom small-scale LEO small-satellite RF systems by using additive manufacturing to reduce costs, material waste, conserve resources, and lower launch mass and energy requirements.